2016
DOI: 10.1002/1873-3468.12521
|View full text |Cite
|
Sign up to set email alerts
|

The F‐box protein FBXL18 promotes glioma progression by promoting K63‐linked ubiquitination of Akt

Abstract: Edited by Kazuhiro Iwai F-box proteins play pivotal roles in multiple cellular processes; however, little is known about their functions in glioma progression. In this study, we found that expression of the F-box and leucine-rich repeat protein 18 (FBXL18) is significantly upregulated in glioma tissues. Depletion of FBXL18 in glioma cells suppresses proliferation and anchorage-independent cell growth, and promotes apoptosis. We also demonstrate that depletion of FBXL18 significantly inhibits Akt activity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…We observed that EGF reproducibly increased Cul1 assembly of not only Skp2, but also βTrCP1 and FBXL18 by >2-fold (Fig 6A; Table S2E), suggesting roles for the latter two proteins in the EGF response. Indeed, FBXL18 has been linked to EGF signaling (Zhang et al, 2017). Western blot analysis revealed that DKO cells had a higher resting level of p-AKT and Skp2•Cul1 complex, but that the EGF-induced assembly of Skp2 with Cul1 was dependent on Cand1/2 and Nedd8 conjugation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that EGF reproducibly increased Cul1 assembly of not only Skp2, but also βTrCP1 and FBXL18 by >2-fold (Fig 6A; Table S2E), suggesting roles for the latter two proteins in the EGF response. Indeed, FBXL18 has been linked to EGF signaling (Zhang et al, 2017). Western blot analysis revealed that DKO cells had a higher resting level of p-AKT and Skp2•Cul1 complex, but that the EGF-induced assembly of Skp2 with Cul1 was dependent on Cand1/2 and Nedd8 conjugation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal expression or dysfunction of several F-box proteins results in aberrant ubiquitination, inducing the development and progression of malignancies, including hematopoietic malignancies. Some F-box family members contribute to tumorigenesis and tumor development 13 15 . Fbxw7 controls leukemia-initiating cells in chronic myelogenous leukemia and chronic myeloid leukemia (CML) by regulating c-Myc ubiquitination 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…F-box proteins promote the ubiquitin-proteasome system ( Halbach et al., 2015 ; Murdoch et al., 2016 ; Sandoval et al., 2015 ; Teixeira et al., 2013 ; Trausch-Azar et al., 2015 ; Yalla et al., 2018 ; Zheng et al., 2016 ) and interact with cell cycle progression ( Randle and Laman, 2016 ; Zhang et al., 2017 ). One F-box protein, FBXW2, has been identified as a housekeeping gene ( Almeida et al., 2014 ), but the functions of FBXW2 are largely unknown.…”
Section: Introductionmentioning
confidence: 99%